FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING - Nany, Magdalena; Santosa, Nina Noviyanti (Universitas Slamet Riyadi, 2021)
More clients needed more public accountant’s services. Public accountant firms will compete each other to get clients. Clients switched their public accountant for various reasons. The objective of this research was to give empirical evidence about the effects of management changes, audit opinion, financial distress, ROA changes, client’s size, public accountant’s size and public ownership on auditor switching both partially and simultaneously. Financial statements data of company listed in Indonesia Stock Exchange were analyzed by logistic regression. The results show that audit opinion, client’s size, public accountant’s size and public ownership partially have significant effect on auditor switching. On the other hand, management changes, financial distress and ROA changes partially do not have significant effect on auditor switching. The result also show that management changes, audit opinion, financial distress, ROA changes, client’s size, public accountant’s size and public ownership simultaneously have significant effect on auditor switching.